Work stress and burnout syndrome during the pandemic in teachers of a Peruvian educational association - VILCHEZ JULON, Juanito (2021)
Most education systems around the world, schools in Peru turned to online teaching in late March 2020, after face-to-face classes were halted due to the outbreak of the COVID-19 pandemic. Although few teachers were prepared to teach their lessons online in this setting, the study aimed to determine the relationship between job stress and burnout syndrome during the pandemic in teachers of a Peruvian educational association. The study was quantitative, correlational, cross-sectional and of a nonexperimental design, where the sample consisted of 105 teachers who were selected through a nonprobabilistic  convenience sampling. The results found reveal that Pearson's correlation coefficient ρ indicates that there is a highly significant positive relationship between stress and Burnout syndrome (ρ = .74; p <.01) and its Emotional Tiredness dimensions (ρ = .77; p <.01), Depersonalization (rho = .58; p <.01) and Lack of Personal Fulfillment (ρ = .49; p <.01). It is concluded that the greater stress in the teaching population, there will be greater burnout syndrome, as well as emotional exhaustion, depersonalization and lack of personal fulfillment during the pandemic.Keywords: Pandemic, work stress, burnout syndrome, emotional exhaustion, depersonalization, lack of personal fulfillment.